Static Voltage Stability Assessment with Reactive Power Compensation in Power System - Shrestha, Chhabindra; Shrestha, Samikshya; Shrestha, Nischal; Adhikari, Santosh; Dharel, Sagar (Journal of Science and Engineering, 2025)
Today, the demand for electricity is increasing rapidly. However, the generation and transmission capability is not growing as fast as it should to meet the demand, leading the power system to operate under severe conditions. This situation raises the problem of instability in the system. Therefore, voltage stability analysis is very essential and a burning concern to properly operate the system. This study performs steady-state voltage stability analysis and analyzes the impact assessment of reactive power compensation on the voltage stability of the Integrated Nepal Power System section, Madhesh Pradesh. Since this region contains most of the industrial load, it seems to be a suitable region for the study of the voltage stability analysis. The analysis was done using PV and QV curves along with the sensitivity analysis and also by using DIgSILENT Powerfactory software. The result showed that implementing reactive power compensation through a 5 MVAr capacitor bank in 132 kV distribution network improved the active power voltage stability margin by a maximum of 8.86%, as observed through loadflow analysis in DigSILENT powerfactory. Additionally, the financial evaluation indicated a payback period of 1.5 years, confirming the economic feasibility of capacitor bank installation.